PENGARUH CITRA MEREK, KEPERCAYAAN, DAN PERSEPSI MANFAAT TERHADAP KEPUTUSAN PEMBELIAN PRODUK LAZADA DI KOTA BATAM - Lissa Maria Lissa; Inda Sukati (SCIENTIA JOURNAL, 2026)
This research aims to analyze the effect of Brand Image, Trust, and Perceived Usefulness on Purchase Decisions of Lazada products in Batam City. This study employs a quantitative approach using a survey method, with data collected through questionnaires distributed to 196 Lazada users. The data were analyzed using SPSS version 26 through multiple linear regression analysis and hypothesis testing. The results show that Brand Image, Trust, and Perceived Usefulness have a significant effect on Purchase Decisions both partially and simultaneously. The coefficient of determination indicates that 93.3% of Purchase Decisions are explained by these variables, while the remaining percentage is influenced by other factors outside this study. These findings suggest that a strong brand image, high consumer trust, and perceived usefulness play a crucial role in influencing consumers’ purchase decisions on Lazada in Batam City